Pengaruh komite audit, likuiditas, leverage , dan aktivitas terhadap financial distress : (Studi Kasus Pada Perusahaan Jasa Sub Keuangan Sektor Asuransi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2017-2022) - Swastika, Desi; Suriyanti, Linda Hetri; Fitriana, Nur (Jurnal Ilmiah Raflesia Akuntansi, 2023)
The purpose of the study was to analyze the effect of the audit committee, liquidity, leverage, and activity on financial distress. This research is a case study on insurance sector sub-financial service companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. This study took secondary data from the financial statements of insurance companies. Technical analysis of data Using Audit Committee analysis, liquidity, leverage, and activity. The analysis concluded that the Audit Committee, liquidity, and leverage had no influence on financial distress. Meanwhile, activities can affect financial ditress in insurance companies. Analysis This study uses 4 independent variables, namely the audit committee, liquidity, leverage, and activity where it can be seen that the Adjusted R Squared value is low at 32.8% so that there are still 67.2% of other variables that are not included in this study. Keywords — financial distress, liquidity, leverage, and activity.